North Rupununi Wildlife Clubs: Makushi Amerindians’ Perceptions of Environmental Education and Positive Youth Development in Guyana - Comber, Julie (Université d'Ottawa / University of Ottawa, 2016)
This doctoral research studied the North Rupununi Wildlife Clubs (NRWC), an Environmental Education (EE) Program for Makushi Amerindian youth in Guyana. The Club format for EE has become popular, and previous research on EE Club programs provide modest support for the hypothesis that EE Club membership increases pro-environmental attitudes and behaviour in children and youth. There is also increasing interest in the role EE Clubs can play in nurturing Positive Youth Development (PYD). This multi-site case study describes EE Clubs in three villages in the North Rupununi of Guyana. Data was collected from semi-structured interviews and focus groups with stakeholders (such as former Club members, volunteers with the Clubs, Elders, and village leaders). The researcher also kept a reflective journal. Findings suggest community members valued the positive impact they perceived participation in NRWC to have on youth and upon their community. Participants offered recommendations on how to improve the program. One of the original findings is that the Clubs may be a way to help reconnect indigenous youth with their elders and restore the transmission of Indigenous Knowledge. These findings contribute to our understanding of EE Clubs and their impact on pro-environmental behaviour, PYD, and communities. This may be relevant to other indigenous communities in isolated rural areas with EE Clubs, and to the field of EE in general.
Keywords: Amerindian; Elders; Clubs; Environmental Education; Guyana; Indigenous; Makushi; Positive Youth Development; Youth